"A THIN DISGUISE": ON ROBERT BROWNING'S FERISHTAH'S FANCIES. Issue 2 (10th May 2016) - Taher-Kermani, Reza
Abstract : Ferishtah's Fancies was a work of Browning's old age, the first of the three volumes he published after he turned seventy, before his death in 1889. All these volumes, but especially the first two, Ferishtah's Fancies (1884 ) and Parleyings with Certain People of Importance in Their Day (1887), are reflective works, in which Browning revisits the major themes and imaginative locations of his life and work. But they are also characteristically restless works, formally complex and innovative, and polemical in spirit. They contain some of Browning's least engaging writing: dense, prickly, mannered, full of a kind of late-Browning poetic lingo which is not quite demotic and not quite high art. Oddly enough, Ferishtah's Fancies was a success when it was published – it is the only volume Browning ever published to be reprinted twice in a year – but this success did not last beyond the First World War, and in modern critical terms it is probably the most neglected of all his work. There are good reasons for this. When you know that Henry Jones based most of his 1912 book, Browning as a Religious and Philosophical Teacher on Ferishtah's Fancies, you can guess what is coming. To Jones what was earnest, profound, and consoling about Browning's ideas was exactly what the next generation rejected with a kind of nausea. Since these ideas no longer came clothed in the verse that had enraptured the Pre-Raphaelites – the verse of Men and Women (1855), Dramatis Personae (1864), and even The Ring and the Book (1868–69) – it failed utterly to make its way into the twentieth century, and has lain buried.